Desirable L-asparaginases for treating cancer and current research trends - Tsegaye, Kindu; Tsehai, Berhanu Andualem; Getie, Birhan (Frontiers in Microbiology, 2024)
Amino acid depletion therapy is a promising approach for cancer treatment. It exploits the differences in the metabolic processes between healthy and cancerous cells. Certain microbial enzymes induce cancer cell apoptosis by removing essential amino acids. L-asparaginase is an enzyme approved by the FDA for the treatment of acute lymphoblastic leukemia. The enzymes currently employed in clinics come from two different sources: Escherichia coli and Erwinia chrysanthemi. Nevertheless, the search for improved enzymes and other sources continues because of several factors, including immunogenicity, in vivo instability, and protease degradation. Before determining whether Lasparaginase is clinically useful, research should consider the Michaelis constant, turnover number, and maximal velocity. The identification of L-asparaginase from microbial sources has been the subject of various studies. The primary goals of this review are to explore the most current approaches used in the search for therapeutically useful L-asparaginases and to establish whether these investigations identified the crucial characteristics of L-asparaginases before declaring their therapeutic potential.